Mengenali Kepribadian Dan Kaitannya Dalam Pemilihan Jurusan Kuliah Bagi Siswa SMA (Universitas Hasyim Asy'ari Tebuireng Jombang, 2022)
Personality is a characteristic that owned by each individual. There are different type of personality, and this makes each individual are unique. And its relation to the choice of majors is very important. By understanding one’s personality, one can determine what majors that matches one’s interest and talent. So that in the future they can develop their talent and achieve what they want.